Offenders with intellectual disabilities in prison: what happens when they leave?. Issue 10 (1st June 2017) - Murphy, G. H.; Chiu, P.; Triantafyllopoulou, P.; Barnoux, M.; Blake, E.; Cooke, J.; Forrester‐Jones, R. V. E.; Gore, N. J.; Beecham, J. K.
Abstract: Background: People with intellectual disabilities, if convicted of offences, may be sentenced to prison, but little is known about their life when they are released. Method: This study followed up men with intellectual disabilities who were leaving prisons in England. Results: The men were hard to contact, but 38 men were interviewed, on average 10 weeks after leaving prison. The men were living in a variety of situations and often were very under‐occupied, with limited social networks. A total of 70% were above the clinical cut‐off for anxiety, and 59.5% were above the clinical cut‐off for depression. The men were receiving little support in the community, and many had been reinterviewed by police. Conclusions: Community teams need to provide better support to this very vulnerable group.